Teeth Care During Pregnancy Period (Mini Review) (Eurasian Medical Research Periodical, 2023)
Pregnancy is a temporary physiology which causes a woman's body to shift her hormones. The consequences are widespread and oral alterations are very common. In the oral cavity, there are a number of particularly significant changes to periodontal diseases. These modifications have major effects, as unfavorable pregnancy results were known. Better understanding of these circumstances by health workers and women might help avoid or minimize these harmful events. Health training is an important strategy to raise awareness of improving oral health among pregnant women. Women in pregnancy, including some with definite signs of oral disease, often do not seek dental care. Preventive, diagnosis and restauratory dental treatment is safe throughout pregnancy and effective to improve and sustain oral health and it is therefore important to educate pregnant women about the prevention and treatment of dental disorder, both for women's oral health and for their children's future oral health.